Peran Penyuluh Agama Terhadap Kerukunan Antar Umat Beragama di Desa Sukoreno Kecamatan Umbulsari Kabupaten Jember - Mahbub Junaidi (FALASIFA : Jurnal Studi Keislaman, 2021)
This study was written to see the village of Sukoreno, Mumbulsari District, Jember Regency, which has the characteristics of biodiversity diversity. The population consists of followers of Islam, Christianity, Hinduism and Hindu culture. This study seeks to examine tolerance in inter-religious relations in the village of Sukoreno Umbulsari, the extent to which harmony between religious communities and how the role of religious extension agents are in caring for and maintaining religious harmony in Sukoreno. This research uses qualitative research methods field research (field reaserch). Community in Sukerone village Umbulsari sub-district is a community consisting of many different ethnicities, cultures, traditions and even traditions, but the attitude of mutual respect, giving freedom of religion, accepting other religions gracefully, and always having a positive attitude between religions. Religious extension workers, as an extension of the government, continue to carry out their duties, from providing counseling to advocating for religious issues to improve the quality of harmony between religious communities. Keywords: Religious Counselor, Inter-Religious Harmony, Sukoreno Umbulsari